Co-infecção vírus da imunodeficiência humana e vírus da hepatite C (HIV/HCV): avaliação da carga viral do vírus da hepatite C - AZEVEDO, Érica Furtado (2023)
It is estimated that worldwide there are over 170 million people infected by hepatitis C virus, 40 million HIV and about 10 million people co-infected where the prevalence of HCV infection are greater in population HIV infected. Approximately 30% of HIV positive patients are also HCV positive. Co-infection HIV/HCV is characterized by the impact of HIV on the natural course of HCV infection and vice versa. HIV causes a more rapid progression of liver disease in individuals infected with HCV, increasing the risk of cirrhosis, as well as the higher rates of viremia by HCV. The HCV has an important role in the management of HIV infection, increasing the risk of liver toxicity caused by antiretroviral drugs. The object of this study is evaluating the viral load of hepatitis C virus (HCV-RNA) in a population of co-infected with HCV and HIV giving the opportunity for early diagnosis, allowing appropriate therapy for hepatitis C in time, thus, preventing progression to liver disease and hepatocellular carcinoma at terminal stage. The patients in this study were 45 co-infected HIV-1/HCV and 100 patients with hepatitis C attended at the program of liver disease of the HFSCMPA, from April 2007 to April 2008. The levels of viral load found HCV-RNA in co-infected group was 6.03 log10 IU / mL (ep = 0.10), which are higher values than in monoinfected 5.69 log10 IU / mL (ep=0,05). No correlation was found between the stage of fibrosis and HCV viral load in both groups.